Results of the ACCEL trial: Dosimetry in accelerated partial breast irradiation. (June 2020) - Quirk, Sarah; Grendarova, Petra; Craighead, Peter; Phan, Tien; Lesiuk, Mark; Pinilla, James; Liu, Hong-Wei; Wilson, Jane; Bignell, Katelyn; Austin, Tammy; Olivotto, Ivo A.; Roumeliotis, Michael
Abstract: Purpose: To report the achieved dosimetry in the ACCEL trial and compare the results to reported dosimetry from the major accelerated partial breast irradiation (APBI) phase III trials. Methods: The ACCEL trial was a single arm, phase II, prospective cohort study. A five-field, inverse-planned, IMRT strategy was employed using a class solution technique to increase planning consistency including high dose conformity and low normal tissue dose to the ipsilateral breast. Results: Between 2016 and 2019, 283 patients were treated with 27 Gy in five fractions in consecutive days. The average PTV conformity index was 1.1. For the ipsilateral breast, the median (range) volume receiving 95% and 50% of the prescription dose was 9.7% (3.2–22.4) and 30.3% (11.1–54.6), respectively. Compared to major APBI phase III trial constraints, this reduction in irradiated volume at the 95% and 50% isodose levels represents a reduction of 209 cm 3 and 265 cm 3, respectively. Conclusion: The IMRT planning strategy employed in the ACCEL trial demonstrated consistent and superior dosimetry by comparison to conventionally used 3D CRT techniques. Future APBI trials should update dosimetric constraints.